The Analysis of Using Verbs in Descriptive Paragraph in Semester I STBA JIA in Academic Year 2021/2022 - Surista, Ade; Lutfiyanti, Winda; Noryatin, Yeni (Sekolah Tinggi Bahasa Asing JIA, 2023)
This research aimed to describe how the students use verbs in their writing descriptive paragraph. The sample uses are the students of semester 1 class B with the total number of students are 21 students. The instrument uses in this research are test and interview. After analyzing, the results shown that in test 1 students score average are 84.2. in test 2 the average of students score is 88.47. in writing descriptive paragraph, the result shown that there are still some students made mistakes in using to be present and past, I joining to be and verbs, in diction, to infinitive, tenses and missing verb. Based on interview, shown that writing is a difficult subject for some the students. Also, They ignore about grammatical rule when they are writing.